The Effect of Environmental, Social, and Governance (ESG) Performance on Dividend Policy in Non-Financial Companies in the ASEAN Capital Market - Julianti; Abdul Moin (LP2M IAIN Palopo, 2026)
This study analyzes the influence of Environmental, Social, and Governance (ESG) performance on dividend policies in 199 non-financial companies listed on the ASEAN-5 capital market during the 2019-2023 period. The background of the research emphasizes the increasing attention of investors to the sustainability of the company and its potential to influence dividend distribution decisions. This quantitative study used panel data regression and probit regression with 995 company-year observations from the Refinitiv Eikon Database. The purposive sampling technique is used to select companies with complete ESG disclosures and reliable financial data. The results showed that the aggregate ESG performance significantly positively affected the Dividend Payout Ratio (coefficient of 0.010216, p=0.000). However, this relationship differs by dimension: the Environmental pillar shows a significant negative impact (coefficient -0.0074334, p=0.000), while the Social pillar (coefficient 0.0067466, p=0.000) and Governance (coefficient 0.0063344, p=0.000) pillar show a significant positive effect. Free Cash Flow emerges as a more important determinant than accounting profitability. In conclusion, the ESG dimension has a differential influence on dividend policy, with significant trade-offs between sustainability investments and dividend distributions varying by ESG type in emerging ASEAN markets.